2009
DOI: 10.1007/s12283-009-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional forward dynamics model of the golf swing

Abstract: Previously, forward dynamic models of the golf swing have been planar, two-dimensional (2D) representations. Research on live golfers has consistently demonstrated that the downswing is not planar. This paper introduces and evaluates the validity of a 3D six-segment forward dynamics model of a golfer. The model incorporates a flexible club shaft and a variable swing plane. A genetic algorithm was developed to optimise the coordination of the model's mathematically represented muscles (torque generators) in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 29 publications
4
50
0
Order By: Relevance
“…In recent studies by Mackenzie and Sprigings [2] and Balzerson et al [3], a four DoF golfer model incorporating a flexible club was shown to provide close comparison to experimental kinematics and kinetics of a low-handicap golfer. This model is represented in Figure 1.…”
Section: Golfer Modelmentioning
confidence: 86%
See 4 more Smart Citations
“…In recent studies by Mackenzie and Sprigings [2] and Balzerson et al [3], a four DoF golfer model incorporating a flexible club was shown to provide close comparison to experimental kinematics and kinetics of a low-handicap golfer. This model is represented in Figure 1.…”
Section: Golfer Modelmentioning
confidence: 86%
“…The flexible beam model was modified to only allow transverse deflection in the swing and droop plane. The magnitude of torsion is minimal compared to the transverse deflection of the club, and therefore was not included in this model [2]. Joint torques were scaled by a force-velocity relationship of muscle, which has been incorporated into previous forward dynamic simulations of the golf swing [2][3][4]12].…”
Section: Optimization Methodsmentioning
confidence: 99%
See 3 more Smart Citations